KORELASI PERHATIAN ORANG TUA DAN HASIL BELAJAR MATEMATIKA - Nada Ayu Deleberti; Mohamad Rif'at; Silvia Sayu (Jurnal AlphaEuclidEdu, 2022)
This study aims .to determine the correlation between parental attention and mathematics learning .outcomes. .The .method .used .in this .research .is .descriptive qualitative method .with correlation .research and ex post facto. The aspects used to .determine whether .there .is a .relationship and .the .level of the .relationship betw.een .two or more variables .in the .study using correlation analysis techniques. .The .subjects in this .study were 36 .students .of class VII E .SMP .Negeri 18 Pontianak. .The object of this .research is the attention of parents and learning outcomes in mathematics. Data collection tools used were questionnaires or questionnaires and documentation. The research data were anal.yzed descriptively. Based .on .the .results of the. research that has been done, it can be concluded that the correlation of parental attention to mathematics learning outcomes is 0.001, where the hypothesis test results show that parental attention correlates significantly with mathematics learning outcomes. The result of the average score of parental attention is 123.89, where as many as 25 students 69.4% have the level of parental attention in the category being processed with the average data on mathematics learning outcomes is 64.11, of which 20 students 55 , 56% have a score of mathematics learning outcomes in the medium category.